2018
DOI: 10.3390/catal8100476
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Glyoxal Oxidase from the Thermophilic Fungus Myceliophthora thermophila M77: Hydrogen Peroxide Production Retained in 5-Hydroxymethylfurfural Oxidation

Abstract: Myceliophthora thermophyla is a thermophilic industrially relevant fungus that secretes an assortment of hydrolytic and oxidative enzymes for lignocellulose degradation. Among them is glyoxal oxidase (MtGLOx), an extracellular oxidoreductase that oxidizes several aldehydes and α-hydroxy carbonyl substrates coupled to the reduction of O2 to H2O2. This copper metalloprotein belongs to a class of enzymes called radical copper oxidases (CRO) and to the “auxiliary activities” subfamily AA5_1 that is based on the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 69 publications
(109 reference statements)
2
27
0
1
Order By: Relevance
“…Significant differences in the kinetic parameters and products’ yields for the oxidation of HMF were observed between the three enzymes, with the highest catalytic efficiency on HMF obtained with Pci GLOX3 ( K cat/ K m = 118.35 s −1 M −1 ). The oxidation of HMF using a phylogenetically different GLOX from Myceliophthora thermophila M77 ( Mt GLOX) has been recently published [32]. Similarly to Pci GLOX described in this paper, low conversion levels were observed with HMF.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Significant differences in the kinetic parameters and products’ yields for the oxidation of HMF were observed between the three enzymes, with the highest catalytic efficiency on HMF obtained with Pci GLOX3 ( K cat/ K m = 118.35 s −1 M −1 ). The oxidation of HMF using a phylogenetically different GLOX from Myceliophthora thermophila M77 ( Mt GLOX) has been recently published [32]. Similarly to Pci GLOX described in this paper, low conversion levels were observed with HMF.…”
Section: Resultsmentioning
confidence: 53%
“…This is the second example of alcohol oxidation by these enzymes, which have been previously found to be active on glycerol [25, 29]. HMF oxidation to DFF as the only product was recently observed with Mt GLOX; however this enzyme was unable to further oxidize DFF in the reaction [32]. Enzymes known to convert HMF to DFF include also AAO, alcohol oxidase, GAO, and HMFO [16, 18, 19, 33, 34] and these enzymes showed higher yields of DFF compared to Pci GLOX.…”
Section: Resultsmentioning
confidence: 84%
“…Select oxidases are capable of sequential oxidation of HMF to the various intermediates shown in Fig. 4 [ 14 , 70 74 ]. Hence, we analyzed the reaction kinetics and products of Fgr AAO and Fox AAO in each of these steps.…”
Section: Resultsmentioning
confidence: 99%
“…Fgr AAO and Fox AAO display similar specificity constants on HMF to the eponymous bacterial HMF oxidase (a GMC superfamily oxidoreductase) [ 73 ], and exhibit higher specificity constants than other enzymes with HMF oxidase activity, including some glyoxal oxidases from AA5_1 (Additional file 1 : Table S5) [ 70 , 71 , 74 ]. However, the recently reported Cgr AAO [ 19 ] has tenfold higher activity on HMF than both Fgr AAO and Fox AAO (Additional file 1 : Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Senger et al successfully analyzed the infrared characterization of [NiFe]-hydrogenase from Escherichia coli HYD-2 by in situ attenuated total reflection Fourier-transform infrared spectroscopy which proved as an efficient and powerful technique for the analysis of biological macromolecules and enzymatic small molecule catalysis [4]. Glyoxal oxidase, an extracellular oxidoreductase that oxidizes aldehydes and α-hydroxy carbonyl substrates coupled to the reduction of O 2 to H 2 O 2 , from Myceliophthora thermophyla, has been characterized by Kadowaki et al [5]. In addition, hydroxylation mechanism of soluble methane monooxygenase from Methylosinus sporium strain 5, a type II methanotrophs, was reported by Park et al, which revealed that two molar equivalents of methane monooxygenase regulatory protein B (MMOB) are necessary to achieve catalytic activities toward a broad range of substrates including alkanes, alkenes, halogens, and aromatics [6].…”
mentioning
confidence: 99%